Analysis of the Experiential Learning Model at SD IT Alam Nurul Islam School in Fostering Disciplinary and Independent Student Characters - Erni Pradita; Thifan Arel Sabila; Nely Anjarwati; Taufik Muhtarom; Cahyaningrum, Elsa Nian; Vina Nabillah (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This research aims to describe the implementation of Experiental Learning model in SD IT Alam Nurul Islam Yogyakarta. This research uses a qualitative approach. The subjects of this research are Principal, Teachers, and Students of SD IT Alam Nurul Islam Yogyakarta. Data collection methods are observation, interview and documentation. This research instrument uses observation guidelines, interview guidelines and documentation. Techniques used to analyze data using qualitative descriptive techniques. The qualitative approach using this descriptive method is used to describe and illustrate and to obtain in-depth meaning regarding the management of experiential learning model learning in the natural school. In addition, to determine the effect of experiential learning model in fostering disciplined and independent character in students.